Some Suggestions on Sino-Nepal Cooperation in Social Construction - Xiang, Su (Kathmandu School of Law Review, 2019)
The current Sino-Nepal cooperation is mainly centered on the fields of politics, economy and trade, culture, security and military affairs. What is sorely lacking is cooperation in social construction which is helpful for deepening the bilateral relationship. From the perspective of social work, the paper puts forward some suggestions on cooperation of social construction such as cultivation of social work professionals, social work service across borders and learning from practical experiences of each other.